Direct self-assembly of Fe2O3/reduced graphene oxide nanocomposite for high-performance lithium-ion batteries1. Issue 21 (7th June 2015) - Xiao, Lisong; Schroeder, Matthias; Kluge, Sebastian; Balducci, Andrea; Hagemann, Ulrich; Schulz, Christof; Wiggers, Hartmut
<x xml:space="preserve">Abstract</x> Fe2O3/rGO nanocomposites were prepared by an electrostatic-interaction-induced self-assembling between the Fe2O3 NPs and the graphene oxide (GO) sheets, followed with a low-temperature hydrothermal reduction process.